Spatial distribution characteristics of the soil thickness on different land use types in the Yimeng Mountain Area, China - Yan, Tingting; Zhao, Weijun; Zhu, Qingke; Xu, Fujin; Gao, Zhikang (Alexandria engineering journal, 2021)
A significant characteristic of the strata in the Yimeng Mountain area is the dual earth-rock structure. Soil thickness directly affects the habitat conditions and is closely related to the survival rate of vegetation. This study aims to reveal the spatial distribution characteristics and influencing factors of the soil thickness in a typical watershed in the Yimeng mountain area. In April 2019, 1816 soil thickness measurements were collected in the Yimeng Mountain area. The differences in the soil thickness, spatial distribution characteristics, and influencing factors of the different land use types were analysed using multivariate statistics and geostatistics. The results revealed the following conclusions. (1) There are significant differences in the soil thicknesses of the different land use types, i.e., farmland (42.63 cm) > forest land (39.26 cm) > grassland (20.35 cm). (2) The optimal semi-variogram model of soil thickness is an exponential model (R2 = 0.914). The ST in the study area has a medium spatial correlation. The high value areas of Populous simonii Carr. and slope farmland and the low value areas of Robinia pseudoacacia L. and grasslands exhibit spatial clustering. (3) The soil thickness varies significantly with land preparation measures, slope direction, and slope position. The high soil thickness values are mainly concentrated on the terrace preparation measures, the half shady slope, and the lower slope. These results provide a scientific basis for improving the survival rate of near-natural vegetation restoration in the Yimeng Mountain area in the earth-rocky mountainous areas of northern China.